ANALISIS PERSEPSI, SIKAP, DAN PERILAKU MASYARAKAT TERHADAP PENCEMARAN AIR DI PELABUHAN KOTA PASURUAN - Maftuha, Mahda Rizqina; Saefudin, Saefudin (EnviroScienteae, 2024)
The Gembong River is a river included in the longest watershed in Pasuruan City with a length of 7.5 km. The estuary of the Gembong River is relatively wide, so it is used as a traditional port. However, the river flow in Pasuruan does not meet the quality standards for class two due to the large number of pollutants from the household and industrial sectors. Based on the results of observations that have been carried out in the Gembong River estuary area or the Pasuruan City port area, it can be seen that there is still some waste, ranging from household waste and plastic waste from snack wrappers. The method used in this study was descriptive qualitative. Data were collected through observation and interviews with 36 respondents. The instruments used in collecting data were questionnaires and interview guidelines. The sampling technique used was purposive sampling. Primary data in the form of analysis of data results regarding aspects of knowledge, attitudes, and actions of the community towards efforts to maintain river sustainability. Secondary data in the form of water quality index and its parameters in the Gembong River estuary area. The results of this study showed that based on the results of the water quality test analysis, it can be seen that the Gembong River is included in the river with lightly polluted criteria. awareness and behavior of the community around the estuary of the Gembong River or the port of Pasuruan City is quite good. However, there is still a need for optimization of the government's work programs in conducting socialization and involving the community in the prevention or control program for river pollution, so that it is hoped that the community can actively participate in protecting the environment.